Varahamihira's braht samhitya. Part 1 - BHAT (M Ramakrishna). (Delhi Motilal Banarsidass Publishers Pvt Ltd., 1986)
The Brhatsamhita of Varahamihira is an encyclopaedia of astrological and other subjects of human interest. This part consists of 50 chapters, from chapters 58 to 107, three Appendices and Index. In chapter 58 units of lineal measurement are given and all the limbs of an idol are described in detail with their measurements. In chapter 60 the ceremony of consecration and installation of idols is described. Physiognomy and Palmistry are treated of in chapters 68-70. In chapter 74 we find excellent erotic poetry with superb imagery. In chapter 75 the author says that a child born to a woman resembles the man whom she thinks of at the time of coitus-a statement yet to be tested by modern psychology and genetics. Chapter 77 shows the author's mathematical genius. Gemology is discussed in chapter 80. In chapter 85 principles of public health and sanitation are highlighted. Chapters 86 to 96 form one big section dealing with omens and auguries. Chapter 104 treats of the effects of planetary transits and also gives a summary of metrics. Chapter 105 deals with rituals. Divided into two parts the book contains Sanskrit text, English translation, explanatory notes and literary comments.
Keywords: Varahamihira; samhitya; s; Part; braht; 1